Functional Topography and Development of Inhibitory Reticulothalamic Barreloid Projections - Imaizumi, Kazuo; Yanagawa, Yuchio; Feng, Guoping; Lee, Charles C. (Frontiers in Neuroanatomy, 2018)
The thalamic reticular nucleus (TRN) is the main source of inhibition to the somatosensory thalamus (ventrobasal nucleus: VB) in mice. However, the functional topography and development of these projections with respect to the VB barreloids has been largely unexplored. In this respect, to assist in the study of these projections, we have utilized a VGAT (vesicular GABA transporter) -Venus transgenic mouse line to develop a brain slice preparation that enables the rapid identification of inhibitory neurons and projections. We demonstrate the utility of our in vitro brain slice preparation for physiologically mapping inhibitory reticulothalamic topography, using laser-scanning photostimulation via glutamate uncaging. Furthermore, we utilized this slice preparation to compare the development of excitatory and inhibitory projections to VB. We found that excitatory projections to the barreloids, created by ascending projections from the brain stem, develop by postnatal day 2-3 (P2-P3). By contrast, inhibitory projections to the barreloids lag 5 days behind excitatory barreloids, developing by P7-P8. We probed this lag in inhibitory projection development through early postnatal whisker lesions. We found that in whisker-lesioned animals, the development of inhibitory projections to the barreloids closed by P4, in register with that of the excitatory projections to the barreloids. Our findings demonstrate both developmental and topographic organizational features of the reticulothalamic projection to the VB barreloids, whose mechanisms can now be further examined utilizing the VGAT-Venus mouse slice preparation that we have characterized.